Resveratrol: An Antiaging Drug with Potential Therapeutic Applications in Treating Diseases - Mercè Pallàs; Daniel Ortuño-Sahagún; Argelia E. Rojas-Mayorquín; Carlos Beas-Zarate; Ester Verdaguer; Antoni Camins; Felix Junyent (MDPI AG, 2009)
The prevention of aging is one of the most fascinating areas in biomedicine. The first step in the development of effective drugs for aging prevention is a knowledge of the biochemical pathways responsible for the cellular aging process. In this context it seems clear that free radicals play a key role in the aging process. However, in recent years it has been demonstrated that the families of enzymes called sirtuins, specifically situin 1 (SIRT1), have an anti-aging action. Thus, the natural compound resveratrol is a natural compound that shows a very strong activation of SIRT1 and also shows antioxidant effects. By activating sirtuin 1, resveratrol modulates the activity of numerous proteins, including peroxisome proliferator-activated receptor coactivator-1α (PGC-1 alpha), the FOXO family, Akt (protein kinase B) and NFκβ. In the present review, we suggest that resveratrol may constitute a potential drug for prevention of ageing and for the treatment of several diseases due to its antioxidant properties and sirtuin activation.